Five new species of the leafhopper genus Limassolla Dlabola (Hemiptera: Cicadellidae: Typhlocybinae) from China - Song, Yuehua; Li, Zizhong (Zootaxa, 2011)
Five new species, Limassolla auriculata sp. nov., L. forcipata sp. nov., L. qianfoensis sp. nov., L. rutila sp. nov. and L. yingjianga sp. nov. from China are described and illustrated. A key and a check list of Chinese species of the genus Limassolla is provided.